2018
DOI: 10.18203/2394-6040.ijcmph20182179
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstetric danger signs among pregnant women attending antenatal clinic at rural health training centre of a medical college in Hyderabad

Abstract: Background: One of the major causes for the death of women is due to maternal mortality. Around 529,000 women die annually from maternal causes (World Health Organization (WHO) estimate) Majority of these deaths occur in the less developed countries. An Indian woman dies from complication related to pregnancy and child birth for every 7 minutes. For every woman who dies =30 more women suffer injuries, infection and disability. In Sub-Saharan Africa, where one of every 16 women dies of pregnancy related causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
1
10
2
Order By: Relevance
“…Regarding the danger signs during labor, our study showed that a higher percentage of women knew prolonged labor was a danger sign. Bhumi et al found that the danger signs recognized by women during the postnatal period were severe bleeding (74.0%), foul-smelling discharge (72.6%), and high fever (68.6%) [19]. Conversely, our study found a higher percentage recognized foul-smelling vaginal discharge as a danger sign, while a lower percentage knew that high fever is a danger sign during the postpartum period.…”
Section: Discussioncontrasting
confidence: 76%
“…Regarding the danger signs during labor, our study showed that a higher percentage of women knew prolonged labor was a danger sign. Bhumi et al found that the danger signs recognized by women during the postnatal period were severe bleeding (74.0%), foul-smelling discharge (72.6%), and high fever (68.6%) [19]. Conversely, our study found a higher percentage recognized foul-smelling vaginal discharge as a danger sign, while a lower percentage knew that high fever is a danger sign during the postpartum period.…”
Section: Discussioncontrasting
confidence: 76%
“…In the present study, 79% of the respondents mentioned placenta not delivered after 30 minutes of child birth as a danger signs during labor and this is consistent with the study done by Bhumi et al, 24 in India (2018) which showed and loss of consciousness as a danger signs during pregnancy. About 95% of respondent were aware of vaginal bleeding as a danger signs followed by decreased or loss of fetal movement (94%) and foul vaginal discharge (94%).…”
Section: Discussionsupporting
confidence: 92%
“…Study conducted by Bhumi MA et al revealed that severe bleeding per vagina (74.0%), foul smelling discharge (72.6%), and high fever (68.6%) were key danger sign during post-natal period known by study participants. 18 Present study revealed that educational status of mother, socioeconomic status of participants and ANC visits were showing statistically significant association with knowledge of obstetric danger signs. Similarly, Vijay et al, found in their study that educational status had significant association with level of knowledge on danger signs during pregnancy and study conducted by Bhumi MA et al, showed that there is a significant association between knowledge scores about danger signs with mother's age and education.…”
Section: Discussionmentioning
confidence: 52%
“…Similar finding was found by Bhumi MA et al in which severe bleeding (71.5%), retained placenta (68.6%), edema hands/feet/face (64.5%) and convulsions (57.6%) were most commonly known. 18 Current study revealed that 42.2% participants had the knowledge of at least one danger sign during postpartum period and 64.8% participants had knowledge about heavy bleeding, 41.5% and 23.2% participants had the knowledge about painful urination and smelly vaginal discharge respectively as a danger sign during this period. Study conducted by Bhumi MA et al revealed that severe bleeding per vagina (74.0%), foul smelling discharge (72.6%), and high fever (68.6%) were key danger sign during post-natal period known by study participants.…”
Section: Discussionmentioning
confidence: 72%